2012
DOI: 10.5120/8773-2704
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Whole-Body-Vibration Exposure to Cairo Subway (Metro) Passengers

Abstract: Vehicles (air, land and water), machinery (for example, those used in industry and agriculture) and industrial activities (such as pilling and blasting), expose people to periodic, random and transient mechanical vibration which can interfere with comfort, activities and health. Metro is one of the important and famous public transportations all over the world. High magnitude of whole-body vibration formed by the Metro may cause diseases and health problems to the human especially a low back pain. It leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The WBV usually cause health and safety risk such as; ride discomfort, badly disturb their performance, back pain, shoulder pain, nausea and other health conditions [9]. WBV also effects on many health risks to the human body such as; physiological system, psychomotor and psychological system [10]. Whenever, there is vibration transmission to whole body of human by means of the vibration source matting with the bottom back or feet of human is always considered as whole-body vibration [11].…”
Section: Introductionmentioning
confidence: 99%
“…The WBV usually cause health and safety risk such as; ride discomfort, badly disturb their performance, back pain, shoulder pain, nausea and other health conditions [9]. WBV also effects on many health risks to the human body such as; physiological system, psychomotor and psychological system [10]. Whenever, there is vibration transmission to whole body of human by means of the vibration source matting with the bottom back or feet of human is always considered as whole-body vibration [11].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] (Ciloglu H et al and Burstorm et al, 2006) have been evaluated. 7,[13][14][15][16][17][18][19] However, the number of conducted researches in the field of exposure to (WBV) with moderate and low severity in jobs like taxi drivers is still limited in Iran. The same limited number of studies on taxi drivers were done according to the basic method.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrations also cause musculoskeletal disorders and spinal injury with more prevalence in some parts of the body such as the shoulders, the neck and the waist [7]. In addition, exposure of driver's whole body to vibrations for long times might has destructive effects on physiological and psychological systems and also cause blurred vision, loss of balance or decrease in caution level [8,9]. De Temmerman et al [10] found that land profile, long period of operation with a machine, agricultural machines' operation speed and the driver's positioning on the seat are the main factors that might cause harm to drivers.…”
Section: Introductionmentioning
confidence: 99%